The critical role of NAT10-mediated N4-acetylcytidine modification in tumor immunity - Li, Chunhong; Jiang, Xiulin; Jia, YingDong; Zhou, Qiang; Yuan, Yixiao; Wang, Qiang (Frontiers in Immunology, 2025)
NAT10, a conserved RNA acetyltransferase, installs N4-acetylcytidine (ac4C) on RNA, thereby regulating stability and translation. Beyond tumor cell proliferation, DNA repair, and chromatin remodeling, NAT10 shapes the tumor immune microenvironment, influencing immune evasion, immune cell infiltration, and responses to immunotherapy. Preclinical studies highlight NAT10 inhibition, such as with Remodelin, as a strategy to enhance cancer treatment-alone or combined with checkpoint blockade, adoptive cell transfer, or chemoradiotherapy. Remaining challenges include in vivo validation, greater inhibitor specificity, and biomarker development. This mini-review synthesizes emerging evidence on NAT10 mechanistic roles in tumor immunity and its promise as a therapeutic target.